Effects of transcranial direct current stimulation on motor learning in healthy individuals: a systematic review - Águida Foerster; Sérgio Rocha; Maria das Graças Rodrigues Araújo; Andrea Lemos; Kátia Monte-Silva
Introduction Transcranial direct current stimulation (tDCS) has been used to modify cortical excitability and promote motor learning. Objective To systematically review published data to investigate the effects of transcranial direct current stimulation on motor learning in healthy individuals. Methods Randomized or quasi-randomized studies that evaluated the tDCS effects on motor learning were included and the risk of bias was examined by Cochrane Collaboration's tool. The following electronic databases were used: PubMed, Scopus, Web of Science, LILACS, CINAHL with no language restriction. Results It was found 160 studies; after reading the title and abstract, 17 of those were selected, but just 4 were included. All studies involved healthy, right-handed adults. All studies assessed motor learning by the Jebsen Taylor Test or by the Serial Finger Tapping Task (SFTT). Almost all studies were randomized and all were blinding for participants. Some studies presented differences at SFTT protocol. Conclusion The result is insufficient to draw conclusions if tDCS influences the motor learning. Furthermore, there was significant heterogeneity of the stimulation parameters used. Further researches are needed to investigate the parameters that are more important for motor learning improvement and measure whether the effects are long-lasting or limited in time.